An extended and fragmented Alfvén zone in the Young Solar Wind. Issue 1 (22nd March 2022) - Chhiber, Rohit; Matthaeus, William H; Usmanov, Arcadi V; Bandyopadhyay, Riddhi; Goldstein, Melvyn L
ABSTRACT: Motivated by theoretical, numerical, and observational evidence, we explore the possibility that the critical transition between sub-Alfvénic flow and super-Alfvénic flow in the solar atmosphere takes place in fragmented and disconnected subvolumes within a general Alfvén critical zone. The initial observations of sub-Alfvénic periods by Parker Solar Probe near 16 R⊙ do not yet provide sufficient evidence to distinguish this possibility from that of a folded surface that separates simply connected regions. Subsequent orbits may well enable such a distinction, but here we use a global magnetohydrodynamic model of the solar wind, coupled to a turbulence transport model, to generate possible realizations of such an Alfvén critical zone. Understanding this transition will inform theories of coronal heating, solar wind origin, solar angular momentum loss, and related physical processes in stellar winds beyond the Sun.